Co-production and Japanese healthcare : work environment, governance, service quality and social values - Pestoff, Victor Alexis (New York, NY : Routledge, 2021)
"Healthcare in most developed countries face a complex and partly contradictory mix of financial, social and political challenges. Fiscal strains combined with New Public Management agendas have caused severe cutbacks and calls for greater efficiency in public healthcare, resulting in a growing concern about service quality. Co-production and Japanese Healthcare explores a possibility to address these issues from a new perspective that emphasizes greater collaboration between the staff and patients. Here professionals and patients/clients act as 'partners to co-produce healthcare through their mutual contributions'. Japan has a unique system of two user-owned healthcare providers with nearly 200 hospitals, 500 clinics and 50,000 beds. However, they differ from each other and from public hospitals, in terms of their work environment, service quality, governance models and social values. This volume compares cooperative and public healthcare providers at ten hospitals across Japan with survey data from the staff, as well as from the patients and volunteers at four hospitals. It will be of interest to researchers, academics, and students in the fields of healthcare management, public and non-profit management, human resource management"--
OCLC-licensed vendor bibliographic record.
Keywords: Medical care -- Japan; Medical policy -- Japan; Health services administration -- Japan; BUSINESS & ECONOMICS / Human Resources & Personnel Management